Empirical Analysis of Government Policies and their Impact on Industrial Sustainability in the GCC - Sadraoui, Tarek; Sallam, Mohamed A. M. (International Journal of Energy Economics and Policy, 2025)
This article analyzes the impact of government policies on industrial sustainability in the Gulf Cooperation Council (GCC) countries in consideration of initiatives for economic diversification, environmental protection regulations, and economic incentives. The GCC countries, traditionally hydrocarbon- reliant, have increasingly adopted policies focusing on sustainability as they transition towards a diversified and more sustainable industrial base. Based on panel data analysis from 2000 to 2023, we study the effectiveness of policy interventions, i.e., investment in renewable energy, tax credits, and green laws, in support of sustainable industrial growth. The findings reveal that visionary government policies contribute significantly to enhancing industrial sustainability, though their efficacy varies under different economic and regulatory policies. Additionally, the study highlights the role of financial market development and foreign direct investment (FDI) in promoting green industrial transitions. The study indicates policy recommendations for GCC nations seeking economic development in harmony with sustainability objectives to achieve long-term industrial stability in the face of a transforming global economy.